In memory "ad perpetuum": An Analysis of Medieval Testaments - Ramos Dias, Marta Miriam (Eikón / Imago, 2014)
The testament is an official document written at times long before death occurs, due to its omnipresence in medieval times, showing not only practical matters related with the dispositions of possessions, but also establishing the manner in which the deceased wants to be remembered and trying to prolong their memory for as long as possible. This paper proposes a simultaneous analysis of attitudes towards death, of moments of the ritual performed in favor of the dead, of the testamentary documents in which are expressed the last wishes and representations in funerary art.